Analysis of Evolutionary Characteristics of Highest Water Levels in Pearl River Guangzhou Reach under Changing Environments - WANG Jin; LIANG Yingshan; LIN Kairong (Renmin Zhujiang)
The evolution characteristics of the highest water levels in the Pearl River are of great significance for the planning and design of flood control works in Guangzhou. By using the moving average method and the Mann-Kendall (M-K) method, the variation characteristics of statistical parameters such as mean value, variance, and coefficient of variation of the highest water level series at four hydrological stations in the Pearl River Guangzhou reach over the years (53~115 a) are analyzed. The highest water level is investigated. The P-Ⅲ type frequency distribution curve is utilized to fit and compare the entire sequence and every 20-year sequence, and the frequency distribution characteristics of future time periods are inferred. The results show that the highest water levels in the Pearl River Guangzhou reach are generally fluctuating and rising, and the mean and variance (and coefficient of variation) of the series are increasing. In recent years, the water levels have repeatedly reached new highs, and the consistency of the hydrological series has been greatly damaged. Traditional hydrological frequency analysis methods using long-series data may produce significant deviations in changing environments. It is suggested that the length of the data series should not be overemphasized, and more attention should be paid to the application of recent data, and the appropriate extension of the trend.